Toward institutionalization of responsible research and innovation: insights from case studies of technological centers in Spain - Hannia Gonzalez-Urango; Carmen Corona-Sobrino; Mónica García-Melón; Pedro Marques (Journal of Responsible Innovation)
The frameworks governing Responsible Research and Innovation (RRI) are heterogeneous and constantly evolving and adapting. We build upon this adaptability to explore the potential development of RRI in Research and Technology Organizations. We explore these issues through a case study of nine Spanish technological centers to analyze the level of commitment to the RRI philosophy. We develop a process-maturity framework to evaluate and understand how these organizations engage with RRI principles. The development of the proposed framework has provided the centers involved with a learning experience as regards their developments and practices in this area. The findings allow us to obtain a holistic and comprehensive view of the responsible behavior of these centers in their innovative activity. Likewise, the results allow us to bridge the gap between theoretical concepts and organizational reality at a meso-level. This process maturity framework is intended to be used as an evaluation methodology and management system.